894 Epidemiology of acute poisoning among children in urban Sri Lanka: the experience of two tertiary care hospitals in Colombo district. (17th August 2022) - Dayasiri, Kavinda; Thadchanamoorthy, V; Jansz, Michael; Dassanayake, Senuri; Anand, Geetha
Abstract : Aims: Acute poisoning in children is associated with increased yet largely preventable morbidity and mortality. Further, poisoning patterns and trends vary over the years in keeping along with change in socio-cultural practices and, availability and access of poisonous substances to young children. This study aimed to describe the recent patterns and trends in acute poisoning among children in two tertiary care centers in urban Sri Lanka. Methods: The current observational cross-sectional study included all children admitted to Lady Ridgeway hospital, Colombo (LRH) and North Colombo Teaching Hospital (NCTH) over a period of two years (January 2020 to December 2021). Data regarding patient demographics, poison types and outcomes were collected retrospectively by trained medical graduates using a based on structured check list by trained medical graduates. All data were recorded using the entered in SPSS 17.0 software. Findings were compared A comparison was made between the findings of the current study with similar the studies performed in rural Sri Lanka; in addition, comparison was also made with data available from and the studies performed in the same settings more than two decades ago. Results: Out of Among 200 children recruited to the study (NCTH – 116, LRH – 84), the majority were male (119 59.5%, range 9 months – 14 years). All poisonings occurred following ingestion and no cases were reported following eye instillation and skin contamination. The majority of poisoning occurred accidentally apart from whilst there're two events of deliberate poisoning. The most common poison type was household chemicals (93, 46.5%) whilst other poison types included pharmaceutical agents (79, 39.5%), plants (16, 8%) and miscellaneous substances (12, 6%). No pesticide poisonings were observed. Common poisons included kerosene oil (37, 18.5%), paracetamol (21, 10.5%), and good luck plants that were thought to bring good fortune (13, 6.5%). The majority of children were discharged following a period of observation whilst one child was admitted to intensive care unit for further management. The observations of the current study showed notable variations in poisoning compared to previous studies performed in urban and rural Sri Lanka over time. They included reduced incidence of pesticide and oleander plant poisonings, and more frequent pharmaceutical poisonings with drugs. Conclusion: The current trends in poisoning among children living in urban Sri Lanka shows decreasing incidence of pesticide poisonings and increasing incidence of poisoning with pharmaceutical agents. Ornamental plants were the most common plants implicated in poisoning in urban regions compared to more toxic oleander plant poisonings observed in rural Sri Lanka. These changing trends in poisonings of children need careful documentation so that it allows for attention in the purview of planning preventative interventions.